Characteristics of Chinese rural networks: Evidence from villages in central China. (January 2017) - Xiong, Hang; Payne, Diane
Characteristics such as 'acquaintance society' and 'differential mode of association' have been widely acknowledged as unique features of Chinese rural societies. However, quantitative evidence of these characteristics is not found in the literature. Applying methods in social network analysis, this paper presents a quantitative study of the social structure of Chinese villages. We measure various network statistics and topological properties of these villages using detailed data on major social relationships (including kinship, house neighbourhood, land plot neighbourhood and political relationships) in 10 rural villages located in central China. In this way, we provide a quantitative description of the structural characteristics of Chinese villages and quantitative evidence for some widely acknowledged features. Our findings are threefold: (1) the networks of Chinese villages are densely connected and highly decentralised; (2) the networks are typical small-world networks, referred to in network research as 'acquaintance societies'; (3) individuals form neighbourhood ties according to the closeness of existing kinship ties, which corroborates the feature of 'differential mode of association'.